2008
DOI: 10.1111/j.1365-2435.2008.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of leukocyte profiles to measure stress in vertebrates: a review for ecologists

Abstract: Summary 1.A growing number of ecologists are turning to the enumeration of white blood cells from blood smears (leukocyte profiles) to assess stress in animals. There has been some inconsistency and controversy in the ecological literature, however, regarding their interpretation. The inconsistencies may stem partly from a lack of information regarding how stress affects leukocytes in different taxa, and partly from a failure on the part of researchers in one discipline to consult potentially informative liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
1,230
19
51

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,221 publications
(1,413 citation statements)
references
References 135 publications
(214 reference statements)
48
1,230
19
51
Order By: Relevance
“…Bańbura et al (2013) examined the heterophil-to-lymphocyte ratio (H/L) in Blue Tits at both our study areas and found that nestlings had on average higher level of the H/L in the urban parkland study area than in the forest study area. The H/L is considered as a reliable indicator of chronic stress reaction in birds (Gross and Siegel 1983;Ots et al 1998;Moreno et al 2002;Davis et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bańbura et al (2013) examined the heterophil-to-lymphocyte ratio (H/L) in Blue Tits at both our study areas and found that nestlings had on average higher level of the H/L in the urban parkland study area than in the forest study area. The H/L is considered as a reliable indicator of chronic stress reaction in birds (Gross and Siegel 1983;Ots et al 1998;Moreno et al 2002;Davis et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, H/L ratio is known to increase in response to parasite load, infectious diseases, starvation or physiological disturbance (Gross and Siegel 1983), and it was suggested to be a more reliable stress indicator in birds than individual cell numbers or corticosterone level (Maxwell 1993). High validity of H/L ratio as a proxy of physiological stress in vertebrates has been recently confirmed with a comparative analysis (Davis et al 2008).…”
Section: Hemoglobin Concentrationsmentioning
confidence: 97%
“…We predicted that under such conditions, large colony size was likely to promote better brood survival by providing reduced predation risk, although these benefits might be accrued at the expense of poorer chick condition (from increased parasitism or social stress). To test the latter prediction, we evaluated growth rates of chicks, as well as their physiological condition expressed with blood hemoglobin concentrations and heterophil/lymphocyte (H/L) ratios, which are considered reliable indicators of physiological stress in birds (Davis et al 2008). In order to confirm whether any potential differences in offspring condition were not genetic, but could be directly attributed to different rearing conditions experienced in the colonies of varying size, a cross-fostering experiment was also conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The hematopoietic tissue is particularly sensitive to environmental changes and is an important indicator of physiological response and stress agents, which are quickly reflected in hematologic parameters (ALLENDER; FRY, 2008;DAVIS;MANEY;MAERZ , 2008;SHUTLER;MARCOGLIESE, 2011). Hematologic and biochemical evaluation of amphibians is of great clinical importance, and provides valuable diagnostic information and understanding of the pathogenesis of diseases, their progression, and response to therapy (SCHMID-SCHÖNBEIN et al, 1980;ALLENDER;FRY, 2008;DAVIS;DURSO, 2009;YOUNG et al, 2012).…”
Section: Introductionmentioning
confidence: 99%